A STUDY OF THE TRENDS, IMPACTS, AND CHALLENGES OF THAI TOURISM IN THE DIGITAL WORLD IN THE NEW NORMAL ERA - Wudhiwiriya, Pornnutcha (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2022)
Due to the digital transformation of the world, digital technology has been widely implemented in various sectors, which is different from the traditional way of life and the implementation of traditional economic and social activities. In the tourism sector, technology and innovation are applied according to the social context. As the social context has changed, the tourism industry has adapted by using new technology and innovation. Therefore, this article presented the use of social media, contactless technology, blockchain, virtual reality, and artificial intelligence in tourism sector. As a result, Thai tourism industry faces significant challenges in strengthening digital capabilities and sustainable tourism. The aim of this article is to present a guideline for how innovation and technology that can be used to assist the tourism industry grow and provide tourists high-quality tourism experiences as well as providing knowledge and understanding for workers and entrepreneurs in the tourism industry in order to deliver quality services with capable of adapting to the new normal of tourism through the integration of government policies on tourism infrastructure and services, as well as sustainable tourism management.